2012
DOI: 10.5840/beq201222224
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Virtue

Abstract: To have a virtue is to possess a certain kind of trait of character that is appropriate in pursuing the moral good at which the virtue aims. Human beings are assumed to be capable of attaining those traits. Yet, a number of scholars are skeptical about the very existence of such character traits. They claim a sizable amount of empirical evidence in their support. This article is concerned with the existence and explanatory power of character as a way to assess the possibility of achieving moral virtue, with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 102 publications
0
71
0
1
Order By: Relevance
“…Furthermore, individual-level virtues have been positioned as both stable traits (e.g. Alzola, 2012;Dahlsgaard, Peterson, & Seligman, 2005), and as fluid, changeable states (e.g. Dutton, Roberts, & Bednar, 2010;Sison, Hartman, & Fontrodona, 2012;Weaver, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, individual-level virtues have been positioned as both stable traits (e.g. Alzola, 2012;Dahlsgaard, Peterson, & Seligman, 2005), and as fluid, changeable states (e.g. Dutton, Roberts, & Bednar, 2010;Sison, Hartman, & Fontrodona, 2012;Weaver, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we will discuss how the work of Aristotle and numerous virtue ethicists that have followed (e.g. Alzola, 2012;Audi, 2012;Beadle, Sison, & Fontrodona, 2015;Fontrodona, Sison, & Bruin, 2013;MacIntyre, 1999;Solomon, 1993), can provide depth to our understanding of virtue. Furthermore, we will integrate a critical realist lens to provide a deep ontology that allows us to clearly articulate the emergent qualities of virtue in a way that captures the depth of AVE while remaining tangible enough to enable further theorizing and empirical investigation within the socially scientific field of POI.…”
Section: Introductionmentioning
confidence: 99%
“…Cavanagh and Bandsuch (2002) expanded this view to argue that virtuous persons, including those in leadership positions, are naturally inclined to enjoy behaving ethically, which is aligned with the notion that they grasp and are especially sensitive to the morally salient features of situations (Alzóla, 2012;Johnson, 2009). Empirically, positive relationships between four Aristotelian cardinal virtues (prudence, fortitude, temperance and justice) and ethical leadership behaviors have been found among managers from a variety of industries (Riggio et al, 2010).…”
Section: Studymentioning
confidence: 99%
“…As reflected in the definitions of the virtues provided earlier, we argue that the expression of virtue is somewhat context dependent, though this is a matter of ongoing debate. For example, both Alzóla (2012) and MacIntyre (1984) argued that holding a virtue entails expressing it across a broad range of situations, while Juurikkala (2012) and Whetstone (2005) suggested that virtuous behavior is at least partially context dependent. Our perspective is in line with their view.…”
Section: A Definition Of Virtuous Leadership Grounded In Virtues Ethicsmentioning
confidence: 99%
See 1 more Smart Citation